2013
DOI: 10.1111/ajop.12047
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of demographic factors associated with stressors and symptoms in African refugees.

Abstract: The objectives of this study were to assess differences in premigration, transit, and resettlement stressor exposure and post traumatic stress disorder (PTSD) symptoms as a function of demographic characteristics (i.e., gender, ethnicity, age, time in United States) and to examine the concurrent and longitudinal relations between stressor exposure and PTSD symptoms. The sample consisted of adult (18-78 years) Somali and Oromo refugee men and women (N = 437). Qualitative data regarding participants' self-nomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…These factors may result in adjustment issues that could increase the odds of MDD among newly arrived refugees. Dissimilar to our findings, previous studies reported poor mental health outcomes among Cambodian, Vietnamese, African, and Sudanese refugees with a longer duration of displacement [ 50 , 51 , 52 , 53 ]. This variation could be due to differences in the type (nationality) of the refugee population, whereby variation in cultural practices and beliefs across the various refugee populations exist.…”
Section: Discussionsupporting
confidence: 83%
“…These factors may result in adjustment issues that could increase the odds of MDD among newly arrived refugees. Dissimilar to our findings, previous studies reported poor mental health outcomes among Cambodian, Vietnamese, African, and Sudanese refugees with a longer duration of displacement [ 50 , 51 , 52 , 53 ]. This variation could be due to differences in the type (nationality) of the refugee population, whereby variation in cultural practices and beliefs across the various refugee populations exist.…”
Section: Discussionsupporting
confidence: 83%
“…Financial challenges can be particularly stressful as monetary assistance during resettlement is often extremely time limited. Further, discrimination related to varying cultural backgrounds and religious affiliations can exacerbate stress (Perera et al, 2013). Indeed, a number of studies have shown the negative impact of post migration living difficulties on psychological and physical outcomes in refugees (Schweitzer et al, 2011;Silove, Steel, McGorry, & Mohan, 1998).…”
Section: Post Migration Living Difficultiesmentioning
confidence: 99%
“…Although newly arrived immigrants in the USA are healthier and have better weight status than their US-born counterparts (9) , their risk for obesity (10) and other chronic diseases (11)(12)(13) increases with longer time in the USA. Immigrant families face stressors stemming from resettlement and adjustment in the host country (14) , including financial realities, language differences, time constraints (15,16) , structural issues such as neighbourhood safety (17) , as well as new weather patterns (18)(19)(20) . Indeed, several studies of immigrants' health have shown that changes in lifestyle behaviours, such as change in diet quality and physical activity (PA), may be contributing to increase in weight, increase in incidence of chronic diseases and decrease in immigrants' perception of their health status (21)(22)(23) .…”
mentioning
confidence: 99%